Effects of Zymosan on Short-Chain Fatty Acid and Gas Production in in vitro Fermentation Models of the Human Intestinal Microbiota - Pi, Xionge; Yu, Zaichun; Yang, Xiaoxia; Du, Zhi; Liu, Wei (Frontiers in Nutrition, 2022)
In this study, the effects of zymosan (HG, hydrolyzed glucan) on the structure and metabolism of fecal microbiota in Chinese healthy people was investigated by an in vitro simulated intestinal microecology fermentation model. We found that HG significantly regulated fecal microbiota composition, including the increase of Bifidobacterium, Faecalibacterium, Prevotella and the decrease of Escherichia-Shigella. Moreover, HG significantly increased the total production of short chain fatty acids (SCFAs) and gases, in which the production of Acetic acid, Propionic acid, CO2, and H2 significantly increased while the production of Isovaleric acid and NH3 significantly decreased. Additionally, the supplement of HG showed certain differences in the regulation of microbiota from four groups. HG significantly increased the relative abundance of Bifidobacterium and significantly decreased the relative abundance of Escherichia-Shigella excluding the older men group. Meanwhile, and the relative abundance of Lactobacillus was significantly increased in young populations. And the relative abundance of Bacteroides was significantly decreased only in the young women. Furthermore, HG significantly increased H2 concentration only in older men. These findings suggest that HG, as a new generation of prebiotics, could regulate the structure of fecal microbiota and its metabolites in a better direction, but when HG participates in precision nutrition formula, it may be necessary to consider the differences in the utilization of different populations.